Competency-based approach in education policy of the state concerning secondary education system - D. E. Shvets (Granì, 2013)
The article deals with the problem of connection of innovation policy and implementation of the Competency-based approach in secondary education. The problem lies in the lack of opportunities to adapt the content of secondary education in the future needs of students, because there is no specialized training in secondary school. At the same time there is an extensive network of different types of educational institutions (lyceums, gymnasiums, kollegiums, etc ), which are in high demand today. However, access to these institutions is limited, entrance to the so-called elite schools, gymnasiums, for example, provides an interview for first graders which has the character of an exam, that identifies the level of knowledge of a child. Today in Ukraine the work concerning discussion the problems of introducing specialized secondary schools in Ukraine has been initiated. On the level of high school it is necessary to create conditions for specialized education both in secondary schools and on the basis of vocational training Besides creating a profile competence school is impossible without proper staff training. Therefore, the Concept of specialized education in high school has been already created and approved by the Academic Council of Pedagogical Sciences of Ukraine and adopted by the Ministry Board of Education and Science, Youth and Sports of Ukraine.